Well-being app to support young people during the COVID-19 pandemic: randomised controlled trial. Issue 5 (19th May 2022) - Thabrew, Hiran; Boggiss, Anna Lynette; Lim, David; Schache, Kiralee; Morunga, Eva; Cao, Nic; Cavadino, Alana; Serlachius, Anna Sofia
Abstract : Objectives: To evaluate the efficacy and acceptability of 'Whitu: seven ways in seven days', a well-being application (app) for young people. Design: Prospective randomised controlled trial of Whitu against waitlist control, with 45 participants in each arm. Participants: 90 New Zealand young people aged 16–30 recruited via a social media advertising campaign. Setting: Participants' homes. Interventions: Developed during the COVID-19 pandemic, and refined from a prototype version that was evaluated during a smaller qualitative study, 'Whitu: seven ways in seven days' is a well-being app that, as its name suggests, contains seven modules to help young people (1) recognise and rate emotions, (2) learn relaxation and mindfulness, (3) practice self-compassion and (4) gratitude, (5) connect with others, (6) care for their physical health and (7) engage in goal-setting. It can be completed within a week or as desired. Main outcome measures: Primary outcomes were changes in well-being on the WHO 5-item Well-Being Index and Short Warwick-Edinburgh Mental Well-Being Scale. Secondary outcomes were changes in depression on the Centre for Epidemiological Studies Depression Scale, anxiety on the Generalised Anxiety Disorder 7-item Scale, self-compassion on the Self Compassion Scale-Short Form, stress on the 10-item Perceived Stress Scale, sleep on the single-item Sleep Quality Scale and user engagement on the end-user version of the Mobile Application Rating Scale and via qualitative feedback during an online survey. Outcomes were evaluated at baseline, 4 weeks (primary study endpoint) and 3 months, and analysed using linear mixed models with group, time and a group–time interaction. Results: At 4 weeks, participants in the Whitu group experienced significantly higher emotional (Mean difference (md) 13.19 (3.96 to 22.42); p=0.005) and mental (md 2.44 (0.27 to 4.61); p=0.027) well-being, self-compassion (md 0.56 (0.28 to 0.83); p<0.001) and sleep (md 1.13 (0.24 to 2.02); p=0.018), and significantly lower stress (md −4.69 (−7.61 to –1.76); p=0.002) and depression (md −5.34 (−10.14 to –0.53); p=0.030), compared with the waitlist controls. Group differences remained statistically significant at 3 months for all outcomes. Symptoms of anxiety were also lower in the intervention group at 4 weeks (p=0.096), with statistically significant differences at 3 months (md −2.31 (−4.54 to –0.08); p=0.042). Usability of Whitu was high (subjective ratings of 4.45 (0.72) and 4.38 (0.79) out of 5 at 4 weeks and 3 months, respectively) and qualitative feedback indicated individual and cultural acceptability of the app. Conclusions: Given the evolving psychological burden of the COVID-19 pandemic, Whitu could provide a clinically effective and scalable means of improving the well-being, mental health and resilience of young people. Replication of current findings with younger individuals and in other settings is planned. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12620000516987).